Implementation and Evaluation of a Unified Turbulence Parameterization Throughout the Canopy and Roughness Sublayer in Noah‐MP Snow Simulations. (18th November 2021) - Abolafia‐Rosenzweig, Ronnie; He, Cenlin; Burns, Sean P.; Chen, Fei
Abstract: The Noah‐MP land surface model (LSM) relies on the Monin‐Obukhov (M‐O) Similarity Theory (MOST) to calculate land‐atmosphere exchanges of water, energy, and momentum fluxes. However, MOST flux‐profile relationships neglect canopy‐induced turbulence in the roughness sublayer (RSL) and parameterize within‐canopy turbulence in an ad hoc manner. We implement a new physics scheme (M‐O‐RSL) into Noah‐MP that explicitly parameterizes turbulence in RSL. We compare Noah‐MP simulations employing the M‐O‐RSL scheme (M‐O‐RSL simulations) and the default M‐O scheme (M‐O simulations) against observations obtained from 647 Snow Telemetry (SNOTEL) stations and two AmeriFlux stations in the western United States. M‐O‐RSL simulations of snow water equivalent (SWE) outperform M‐O simulations over 64% and 69% of SNOTEL sites in terms of root‐mean‐square‐error (RMSE) and correlation, respectively. The largest improvements in skill for M‐O‐RSL occur over closed shrubland sites, and the largest degradations in skill occur over deciduous broadleaf forest sites. Differences between M‐O and M‐O‐RSL simulated snowpack are primarily attributable to differences in aerodynamic conductance for heat underneath the canopy top, which modulates sensible heat flux. Differences between M‐O and M‐O‐RSL within‐canopy and below‐canopy sensible heat fluxes affect the amount of heat transported into snowpack and hence change snowmelt when temperatures are close to or above the melting point. The surface energy budget analysis over two AmeriFlux stations shows that differences between M‐O and M‐O‐RSL simulations can be smaller than other model biases (e.g., surface albedo). We intend for the M‐O‐RSL physics scheme to improve performance and uncertainty estimates in weather and hydrological applications that rely on Noah‐MP. Plain Language Summary: Most widely used computer models of the land surface neglect canopy‐induced turbulence in calculations of heat, water, and momentum exchanges. Accounting for canopy‐induced turbulence is important because coherent eddies that form near the canopy top are responsible for generating most of the transportation of heat, water, and momentum, in and directly above the canopy. In 2007, 2008 scientists Ian N. Harman and John J. Finnigan developed a methodology that adapts contemporarily used equations in operational LSMs to account for canopy‐induced turbulence. In this study, we create a new physics option for the Noah with Multi‐Parameterization (Noah‐MP) LSM that accounts for canopy‐induced turbulence based on the Harman and Finnigan, 2007–2008 methodology. The primary focus of this study is to quantify differences between Noah‐MP snowpack simulations using the classical physics option that neglects canopy‐induced turbulence with the new physics option that accounts for canopy‐induced turbulence. Overall, simulations using the new physics option tend to have better agreement with ground‐based SWE observations across 647 validation sites within the western United States. We intend for the new physics scheme to improve weather and hydrological applications for operational modeling systems that rely on the Noah‐MP LSM. Key Points: This study presents a new physics option for Noah‐MP that accounts for canopy‐induced turbulence in the roughness sublayer Simulated SWE over shrublands using the new turbulence scheme agree more with observations than those using the traditional MOST scheme Differences in snow simulations are mainly attributable to differences in aerodynamic resistance to sensible heat below the canopy top